Analysis of Treatment Profile, Direct Medical Costs, and Quality of Life in Hemodialysis Patients in Hospital X in Banten - Lucky Dita Agustiansyah; Prih Sarnianto; Yusi Anggraini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Chronic kidney failure (CRF) is one of the world's health problems because its prevalence continues to increase. There was a 4-fold increase in new patients and a 16-fold increase in active patients from 2007 to 2015. Payments made by BPJS use the INA-CBGs system. This study was conducted to see the feasibility of the real treatment profile compared to the Pernefri standard (Indonesian Nephrology Association) and the cost consequences compared to the Ina-CBGs rate, as well as to see the factors that affect the patient's quality of life. This type of research is an observational study with a cross-sectional design. Treatment profile data were taken retrospectively from medical records. Direct cost data were taken retrospectively from patient treatment documents. Patient's quality of life data was collected prospectively from in-person interviews using a validated EQ-5D questionnaire. The results showed that the sexes were 43 males and 35 females, with the largest age range> 50 years, retirees and IRT, junior high school / high school education, the most marital status was married. Based on the treatment profile of the incompatibility of EPO therapy with a Hb between 8 g, dL-10 g / dL was not given EPO. Based on the calculation of real medical costs of Rp. 660,529, which is less than the ideal medical cost of Rp. 778,786 and the tariff for Ina-CBG is Rp. 879,100. Quality of life of patients with CRF have a sufficient quality of life with a mean value of 63.01% (p <0.05, Linear regression)